PKM Pembuatan dan Uji Coba Media Pembelajaran Trainer Sensor bagi Guru Elektronika SMKN 2 Makassar - Purnamawati; Muhammad Akil; Nuridayanti; Ridwansyah; Mustamin Tewa (Sakura Digital Nusantara, 2023)
The purpose of this service activity is to provide solutions to overcome the problems faced by productive teachers majoring in electronics engineering at SMK Negeri 2 Makassar including designing learning media in the form of sensor and transducer trainers, providing material related to the development of learning media, providing material and training related to learning media in the form of trainers, and provide materials and training related to the use of sensor and transducer trainers. The method of implementing this activity is design, definition, manufacture and deployment. Furthermore, to determine the achievement of this activity (whether the output of this activity is of good quality to be used as material in designing learning media development patterns), it is necessary to evaluate the implementation of activities during the activity process and after the end of the activity. Evaluation of this media was carried out by conducting trials on productive teachers at SMK Negeri 2 Makassar. The results of an evaluation of the level of partner satisfaction can be seen in Figure 3. with P1 to P10 being statement items given to partners covering PkM themes, PkM materials, benefits, community needs, planning, monitoring and evaluation, budget use, application of PkM results, exchange of information and follow-up of PkM activities. Statements about the usefulness of implementing PkM activities got 59% who answered very satisfied, the remaining 41% answered satisfied with the benefits of PkM. In addition, the statement regarding the exchange of information that occurred during the implementation of the PkM obtained a percentage of 53% very satisfied and 47% said they were satisfied.